(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
Prefixes by which adjectives were created in an Old Ukrainian language are described in the article, the origin and relations of Ukrainian prefixes with Old Slavonic and other Slavonic languages are investigated.